Increasing Tokopedia customer loyalty through electronic service quality dimensions with customer trust as intervening / Iqbal Reza Pratama and Alifah Ratnawati - Pratama, Iqbal Reza; Ratnawati, Alifah (2022)
Tokopedia is one of the e-commerce sites in Indonesia that is used by the public and business owners to manage their online store business easily and cheaply. This study aims to analyze the effect of electronic service quality on customer loyalty at Tokopedia with customer trust as an intervening variable. The data used in this study are primary data and secondary data. Primary data was obtained by distributing questionnaires to respondents. The number of respondents used is 230 respondents. Meanwhile, secondary data was obtained by conducting a desk study on books, journals, and articles related to the research variables. The analytical method used is a structural equation model with the help of AMOS software version 22. Based on the results of the study, it can be concluded that there is no significant effect between compensation as a dimension of electronic service quality on Tokopedia customer trust in Semarang; there is a significant influence between responsiveness as a dimension of electronic service quality on the trust of Tokopedia customers in Semarang; there is a significant influence between site operations as a dimension of electronic service quality on the trust of Tokopedia customers in Semarang; there is no significant effect between reliability as a dimension of electronic service quality on the trust of Tokopedia customers in Semarang. There is no significant effect between compensation as a dimension of electronic service quality on Tokopedia customer loyalty in Semarang; there is a significant influence between responsiveness as a dimension of electronic service quality on Tokopedia customer loyalty in Semarang; there is a significant influence between site operations as a dimension of electronic service quality on Tokopedia customer loyalty in Semarang; There is a significant influence between reliability as a dimension of electronic service quality on Tokopedia customer loyalty in Semarang. Customer trust does not meet the criteria to be said to be an intervening variable. The managerial implication of this research is that Tokopedia can pay more attention to responsiveness by providing procedures related to sellers in responding to orders from customers. Furthermore, Tokopedia can provide a time limit for a seller to respond to customer requests. Tokopedia can also improve site operations to increase customer trust and loyalty. This attention can be in the form of developing the features available on Tokopedia application and website.